2008
DOI: 10.1002/jbt.20242
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl diselenide protects against hematological and immunological alterations induced by mercury in mice

Abstract: Mercury is a heavy metal that can cause a variety of toxic effects on the organism, such as hematological and immunological alterations. In the present investigation, deleterious effects of mercury-intoxication in mice and a possible protective effect of diphenyl diselenide (PhSe)(2) were studied. Male adult Swiss albino mice received daily a pretreatment with (PhSe)(2) (15.6 mg/kg, orally) for 1 week. After this week, mice received daily mercuric chloride (1 mg/kg, subcutaneously) for 2 weeks. A number of hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
(69 reference statements)
2
9
0
Order By: Relevance
“…The pretreatment with diphenyl diselenide was effective in protecting against the immunological and hematological alterations induced by HgCl 2 in mice. 52 Following a very similar protocol, the effect of combined therapy with diphenyl diselenide and 2,3-dimercaptopropane-1-sulfonic acid (DMPS) was investigated against toxicity induced by HgCl 2 in mice. The results proved that combined therapy with diphenyl diselenide and DMPS was less effective than isolated therapies to counteract renal and hematological damage induced by HgCl 2 in mice.…”
Section: Mercurymentioning
confidence: 99%
“…The pretreatment with diphenyl diselenide was effective in protecting against the immunological and hematological alterations induced by HgCl 2 in mice. 52 Following a very similar protocol, the effect of combined therapy with diphenyl diselenide and 2,3-dimercaptopropane-1-sulfonic acid (DMPS) was investigated against toxicity induced by HgCl 2 in mice. The results proved that combined therapy with diphenyl diselenide and DMPS was less effective than isolated therapies to counteract renal and hematological damage induced by HgCl 2 in mice.…”
Section: Mercurymentioning
confidence: 99%
“…Our research group demonstrated toxic effects of the HgCl 2 + (PhSe) 2 interaction in mice, after a concomitant administration to both compounds (Brandão et al , ). In contrast, when (PhSe) 2 was administered before or after HgCl 2 exposure, beneficial effects were observed in mice (Brandão et al , ). This may suggest that the effects of (PhSe) 2 against the toxicity induced by mercury depends on dose of this organoselenium compound and whether the administration of both compounds is concomitant or not.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have reported, in previous studies, that the co‐administration of HgCl 2 and (PhSe) 2 in mice can be related to the toxicity to both compounds (Brandão et al , ). In contrast, when (PhSe) 2 is administered before or after HgCl 2 exposure, beneficial effects were demonstrated (Brandão et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that DPDS can protect against some toxic effects of MeHg in mice [62]. Furthermore, DPDS protected against the observed reduction in some haematological immunological alterations induced by mercury in mice [73]. In combination with N-acetyl cysteine, (NAC), DPDS was reported to be partially effective in protecting against the effects of mercury.…”
Section: Organoseleniums: Promising Intervention In Mercury Toxicitymentioning
confidence: 99%